The effect of diethylcarbamazine in a murine model of Brugia malayi microfilaraemia - Neill, M. (1979)
The effect of diethylcarbamazine was tested in a murine model of Brugia malayi microfilaraemia. A course of therapy similar to that used to treat human infection led to more than a 90% decrease in circulating parasites. Experiments in which different amounts of diethylcarbamazine were given as a single dose indicated that its microfilaricidal activity is dose-dependent. The animal model of B. malayi microfilaraemia may be useful for studies of the mechanism of action and pharmacology of diethylcarbamazine and may be applied to the screening of new microfilaricidal drugs.